ON SEMI GENERALIZED CARTAN G-SPACE - Al-Sheikhly, Anmar Hashim Jasim (Al-Nahrain Journal of Science, 2010)
following results:(i) A Cartan G-space is semi generalized Cartan.(ii) A semi Cartan G-space is semi generalized Cartan.(iii)We study this space (semi generalized Cartan G-space) and give enough examples and theoremsabout it, where we study its properties, subspace, and the equivariant homeomorphic image.(iv) We prove that a G-space X is semi generalized Cartan if X has a star thin semi generalizedopen set.